Modeling, analysis and control of an inertial wave energy converter and hydraulic power take-off unit - Han Jia; Zhongcai Pei; Zhiyong Tang; Meng Li (Scientific Reports, 2025)
Abstract A wave energy converter (WEC) utilizing the inertial gyroscope coupled with a hydraulic power take-off (PTO) unit for energy transformation and application is investigated. The structure design of various components of WEC are introduced. Power is obtained by the dynamic response of the floating body under the excitation of wave energy, and converted into gyroscopic precession in the form of swing angle and torque, and directly to drive the hydraulic pump module of the hydraulic PTO system to output the hydraulic energy. The fluctuation of pressure and flow in the hydraulic PTO system can be adjusted and smoothed by means of the accumulator, which can effectively improve power output stationarity of the hydraulic motor-generator. The mathematical models of energy conversion and transmission process encompassing the wave-to-hydraulic PTO unit are established. The impact rules of major variables in the gyroscope and hydraulic PTO unit acting on WEC system are investigated by numerical simulations. It can provide scientific basis for optimizing utilization of this wave energy conversion system, and provide mathematical guidance for the optimization control of the WEC system. To improve the computation real time and control precision of power output of the hydraulic motor-generator unit, an Adaptive Hierarchical Model Predictive Control (AHMPC) method is proposed and put into used. The AHMPC strategy utilizes a larger wave prediction sequence level to solve the offline unconstrained energy maximization control problem, and then a smaller level to deal with the online constraints. The AHMPC method saves 3 times the computation time compared to the traditional MPC method, reduces the energy fluctuation amplitude in the system by 96%, so that the hydraulic motor-generator can operate at the desired speed based on the available wave forecast information while satisfying the state constraints.